Efeito da adição de colágeno hidrolisado, cloreto de potássio e arginina na qualidade de mortadelas com reduzido teor de sódio e gordura - Corrêa, Letícia Pereira (2025)
The mortadella sausages were reformulated by replacing animal fat with hydrolyzed collagen (HC) at concentrations of 50% and 70%, replacing 50% of NaCl with KCl, and adding 1% arginine. The effects of these changes were evaluated in relation to the physicochemical properties, sensory attributes, and shelf life of the products during 60 days of storage at 4°C. The results indicated that replacing 50% and 70% of fat with HC reduced fat content by 42.6% and 55.3%, respectively, while increasing protein levels by 37% and 55%. Replacing 50% of NaCl with KCl led to a 33.2% reduction in sodium content and a 234.7% increase in potassium content. The replacement of 50% of fat by HC was the most effective, as it maintained the sensory attributes and structural integrity of the products, while the replacement of 70% compromised the texture and flavor. Although the replacement of NaCl by KCl generated sensory defects, such as bitter and metallic flavors, the addition of arginine was effective in masking these effects, resulting in a sensory quality similar to that of the control. Oxidative stability, measured by TBARS values and sensory evaluations, was maintained consistently in all treatments throughout storage. The count of aerobic mesophilic microorganisms and lactic acid bacteria evolved similarly in the reformulated and control products, ensuring microbiological stability. pH levels remained constant in all treatments, and color stability, assessed by ΔE values, was preserved during storage, with differences visible only on day 60. These results demonstrate the feasibility of reformulating mortadella with HC, KCl and arginine, offering a healthier product.